Assessing quality of experience for manipulation modes in virtual reality interaction - Gangling Liu; Rusmadiah Bin Anwar; Verly Veto Vermol (Cogent Arts & Humanities)
Driven by the concept of the metaverse, virtual reality technology has made significant advancements, thereby inspiring the academic community to delve into the quality of user experience (QoE) in VR. In reviewing the literature on VR interaction techniques and QoE evaluation methods, this study identified six key QoE features that impact VR interaction and manipulation experiences. It also identified three types of fundamental interaction tasks and their corresponding manipulation modes. Based on these findings, a within-subjects design experiment was conducted to evaluate the QoE of different VR manipulation modes. By using a combination of questionnaire and interview, data from 73 participants were collected and analyzed. The results showed that users preferred manipulation modes that simulate real-world operations due to their high realism, dependability, perspicuity, and operational comfort. The findings further indicated that appropriately integrating non-isomorphic operations can enhance efficiency without sacrificing comfort, while also adding fun and novelty to the experience. The results of this paper provide more accurate interaction design guidelines for designers and program developers working with VR manipulation modes.